An Anatomical variation of Flexor Hallucis Longus with two extra slips (AYUSHDHARA, 2025)
Flexor hallucis longus (FHL), a key toe flexor muscle, located on the posterior aspect of the fibula below the deep fascia of the calf. It originates from lower two-thirds of posterior surface of fibula and inserts at the base of distal phalanx of great toe. Background: Anatomical variations in the plantar musculotendinous architecture, particularly at the Chiasma Plantare (Master Knot of Henry), can influence foot biomechanics and have surgical significance. Main Clinical Findings: During routine cadaveric dissection, a rare unilateral variant was identified in which two tendinous slips originated from the flexor hallucis longus (FHL) tendon and merged with the flexor digitorum longus (FDL) tendons inserting at base of the distal phalanx of second, third, toes. The slips arose deep to the quadratus plantae at the classical FHL–FDL crossover. Discussion: This configuration corresponds to Type I-b of Plaass et al.’s classification and may contribute to enhanced toe flexion strength, improved force distribution, and functional redundancy. Such variations have surgical relevance during tendon grafting, Achilles tendon reconstruction, and in managing tibialis posterior dysfunction. Conclusion: Documenting such rare patterns enriches anatomical databases, aids preoperative planning, and deepens our understanding of plantar biomechanics.